FLOW AND OPTIMAL EXPERIENCE: METHODOLOGICAL IMPLICATIONS FOR INTERNATIONALIZINGAND CONTEXTUALIZING A POSITIVE PSYCHOLOGY CONCEPT. PART 1 - Grant Rich (Peoples' Friendship University of Russia (RUDN University), 2016)
This article represents the first part of a two part series of articles focusing upon one core positive psychology concept - the peak experience termed flow developed by psychologist Mihaly Csikszentmihalyi - as a test case for examining some of the issues involved when positive psychology is internationalized and made indigenous. In particular, methodological, measurement, and theoretical issues regarding flow research will be discussed. Quantitative, qualitative and mixed methods approaches to flow, including interviews, surveys, and the experience sampling method among others will be described. Evidence is examined from a range of existing research projects on flow from around the globe, raising questions concerning the positive psychology enterprise, including the value of psychological assessment tools and the debate over cross-cultural universals/comparisons. Rather than viewing qualitative and quantitative approaches (or anthropological and psychological perspectives) as rival factions, this project seeks to develop constructive dialogue that acknowledges both strengths and limitations of each approach to facilitate engagement with the topics of mixed methods and human strengths, subjects often neglected in cross-cultural research. The first part of the article series examines methodological implications of this positive psychology concept, and the second part of the article series focuses upon the cross-cultural implications.